Bisimulations for Asynchronous Mobile Processes - Hansen, Martin; Hüttel, Hans; Kleist, Josva (BRICS Report Series, 1996)
Within the past few years there has been renewed interest in the study of value-passing process calculi as a consequence of the emergence of the pi-calculus. Here, [MPW89] have determined two variants of the notion of bisimulation, late and early bisimilarity. Most recently [San93] has proposed the new notion of open bisimulation equivalence. In this paper we consider Plain LAL, a mobile process calculus which differs from the pi-calculus in the sense that the communication of data values happens asynchronously. The surprising result is that in the presence of asynchrony, the open, late and early bisimulation equivalences coincide - this in contrast to the pi-calculus where they are distinct. The result allows us to formulate a common equational theory which is sound and complete for finite terms of Plain LAL.